2014
DOI: 10.1016/s1995-7645(13)60196-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of E-cadherin, N-cadherin, transforming growth factor-β1 and Twist in prostate cancer

Abstract: The reduced expression of E-cadherin, abnormal expression of N-cadherin, transformation form E-cadherin to N-cadherin and the increased expression of TGF-β1 and Twist play an important role in the occurrence and development of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
5
29
0
2
Order By: Relevance
“…It has been shown that the blockage of TGF-β causes upregulation of E-cadherin resulting in the reduction of migration and invasion of carcinoma cells 38 and then TGF-β1 expression negatively correlated with E-cadherin expression. 39 Our results are consistent with the literature in terms of elevated serum TGF-β1 levels and reduced sEcadherin levels. It was assumed that increased TGF-β1 levels may be associated with decreased E-Cadherin expression in endometrial and ovarian cancers.…”
Section: Turan Et Al Vitronectin Se-cadherin and Tgf-β1 Levels In Esupporting
confidence: 92%
“…It has been shown that the blockage of TGF-β causes upregulation of E-cadherin resulting in the reduction of migration and invasion of carcinoma cells 38 and then TGF-β1 expression negatively correlated with E-cadherin expression. 39 Our results are consistent with the literature in terms of elevated serum TGF-β1 levels and reduced sEcadherin levels. It was assumed that increased TGF-β1 levels may be associated with decreased E-Cadherin expression in endometrial and ovarian cancers.…”
Section: Turan Et Al Vitronectin Se-cadherin and Tgf-β1 Levels In Esupporting
confidence: 92%
“…Increased expression of both TGFβ and Twist are associated with the cadherin switch in EMT and play an important role in the development of PCa [23]. The role of Twist in the down-modulation of E-cadherin is well-established and Twist expression has been shown to predict the metastatic potential of primary PCa [46].…”
Section: Resultsmentioning
confidence: 99%
“…[5] This protein is mainly expressed in the cytoplasm and plasma membrane and is upregulated in response to lesions. [20,21] Ishimine et al, found that N-cadherin can serve as a prospective marker on the plasma membrane of human mesenchymal stem cells, as it may promote the differentiation of cardiomyocytes. When cardiomyogenic progenitor cells differentiate into mature cardiomyocytes, high levels of N-cadherin expression are observed, which play an essential role for the formation of cardiac intercalated disk structure.…”
Section: N-cadherinmentioning
confidence: 99%